The Classification of Knowledge Based on Al-Ghazali's Perspective and Its Relevance to Qur’anic Exegesis - Akbar, Rizamul Malik; Soleh, Achmad Khudori (STIT Sunan Giri Bima, 2025)
This article studies Al-Ghazali’s system of knowledge classification and its relevance to Qur’anic exegesis within the framework of classical Islamic epistemology. The focus of this study is to explain the structure of Al-Ghazali’s epistemology, which includes the sources of knowledge, methods of acquisition, and legal-ethical rulings on seeking knowledge, while positioning tafsir as an integral part of this framework. This research employs a qualitative approach through library research, focusing on Al-Ghazali’s major works, such as Iḥyā’ ‘Ulūm al-Dīn and al-Risālah al-Ladunniyyah. The findings indicate that: (1) Al-Ghazali classifies knowledge based on its sources into revelatory knowledge (‘ilm al-shar‘i), rational knowledge (‘ilm al-‘aql), and intuitive knowledge (‘ilm al-kashf); (2) based on its method of acquisition, knowledge is divided into ḥuḍūrī (immediate) and ḥuṣūlī (acquired through learning), incorporating approaches such as bayānī, burhānī, ‘irfānī, and tajribī; (3) in terms of legal rulings, knowledge is categorized as farḍ ‘ayn, farḍ kifāyah, mandūb, mubāḥ, or ḥarām; and (4) Qur’anic exegesis is positioned as a shar‘i science, falling under the category of farḍ kifāyah, specifically within the subcategory of al-mutammimāt, developed through ḥuṣūlī methods and integrating several epistemological approaches.